2008
DOI: 10.1037/a0012593
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive inhibition and working memory in attention-deficit/hyperactivity disorder.

Abstract: Studies of cognitive control in attention-deficit/hyperactivity disorder (ADHD) have emphasized the ability to suppress motor responses (i.e., behavioral inhibition) rather than the ability to actively suppress prepotent mental representations (i.e., cognitive inhibition). Further, working memory deficits are suspected in ADHD, yet their distinction from cognitive inhibition is unclear. Two hundred and eighty-eight adolescent and adult participants, 115 of whom met criteria for ADHD and 173 of whom were for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 76 publications
7
44
1
2
Order By: Relevance
“…Additionally, it was shown that clinicians could increase therapeutic outcomes by addressing the attending issues prior to the initiation of speech modification therapy (Riley & Riley, 1979). These findings are relevant as evidence accumulates on the association between stuttering and attention skills (Blood et al, 2007;Bosshardt, 2006;Engelhardt et al, 2008Engelhardt et al, , 2010Heitmann et al, 2004).…”
Section: Adhd and Stutteringmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, it was shown that clinicians could increase therapeutic outcomes by addressing the attending issues prior to the initiation of speech modification therapy (Riley & Riley, 1979). These findings are relevant as evidence accumulates on the association between stuttering and attention skills (Blood et al, 2007;Bosshardt, 2006;Engelhardt et al, 2008Engelhardt et al, , 2010Heitmann et al, 2004).…”
Section: Adhd and Stutteringmentioning
confidence: 94%
“…ADHD often co-occurs with both affective disorders (Cuffe, Moore, & McKeown, 2005) and learning disability (Al-Yogan, 2009;Capano, Minden, Chen, Scharchar, & Ickowicz, 2008;Eden & Vaidia, 2008;Mayers, Calhoun, & Crowell, 2000). This complex relationship between the core symptoms of ADHD and neurocognitive functioning has been shown to contribute to difficulties with the efficient production of language (Blood, Blood, Maloney, Weaver, & Shaffer, 2007;Engelhardt, Corley, Nigg, & Ferreira, 2010;Engelhardt, Nigg, Ferreira, & Carr, 2008;Heitmann, Asbjørnsen, & Helland, 2004). These language-based issues can include excessive language production, poor topic maintenance and difficulty with sequencing and organization.…”
Section: Introductionmentioning
confidence: 96%
“…This is an important consideration given that working memory has often been problematic among ADHD samples (Alderson et al, 2010;Engelhardt et al, 2008;Gropper and Tannock, 2009;Kasper et al, 2012;Katz et al, 2011;Martinussen et al, 2005). In one study, researchers did not find a relationship between long term allocentric visual memory difficulties and working memory among temporal lobectomy patients (Feigenbaum and Morris, 2004).…”
Section: Visual Memorymentioning
confidence: 96%
“…Brevemente, la inhibición perceptual sería el proceso responsable de suprimir estímulos irrelevantes del ambien te; la inhibición cognitiva tiene como fun ción disminuir las representaciones de ca rácter intrusivo e irrelevantes para el logro de las metas actuales; la inhibición comportamental es la responsable de suprimir respuestas o impulsos prepotentes e inapropiados para la actividad en curso (Diamond, 2013). En consonancia con este enfoque, distintos autores han planteado la necesidad de analizar otros tipos inhibitorios además de la inhibición comportamental en el TDAH (Bé dard, Trampush, Newcorn & Halperin, 2010;Engelhardt, Nigg, Carr & Ferreira, 2008).…”
Section: La Inhibición Como Constructo Multidimensionalunclassified
“…Los resultados obtenidos en el desempeño en la tarea de inhibición cognitiva son consistentes con diferentes estudios que encuentran un funcionamiento normal en la supresión de representaciones mentales en esta cla se de tareas en niños con TDAH (Engelhardt et al, 2008;Rubia, Smith, Taylor & Brammer, 2007). Teniendo en cuenta el modelo tripartito de la inhibición (perceptual, cog nitiva y comportamental) sobre el que se desarrolla la Batería TAC, estos resultados son relevantes ya que muestran un compromiso diferencial según el tipo de proceso inhibitorio considerado.…”
Section: Validez De Grupos Contrastados En Procesos Ejecutivosunclassified